Fuzzy logic control of a hybrid PV/battery/diesel generator system integrated in an electrical network: case study of City of Douala - Bading Epanda, Alain; Nyobe Yome, Jean Maurice; Thierry Sosso, Olivier; Ele, Pierre (Institute of Advanced Engineering and Science, 2025)
The control of hybrid systems is a considerable challenge for the energy supply to consumers. For this purpose, this study implemented an intelligent control for a hybrid system connected to the electrical grid to meet the energy demand of a building in the city of Douala, Cameroon. In this work, an intelligent management system using fuzzy logic is proposed to overcome the challenges of this multi-source integration. The proposed method based on a fuzzy logic controller makes it possible to optimize the performance of the energy sources used with a coordination system. Thus, it makes it possible to adjust in real time the system control process based on climatic conditions and the characteristics of the storage devices in order to provide an adequate adaptive control strategy. Furthermore, this system effectively balances the energy supply from all sources. MATLAB/Simulink software and real building data are used to simulate the proposed intelligent management strategy. The results obtained indicate that energy is efficiently supplied to consumers with efficiency of 98% and reduction of fuel consumption of 45% based on the availability of the sources, thus demonstrating the benefits of the control strategy based on fuzzy logic for balanced system operation.